2018
DOI: 10.1017/s2040174417001064
|View full text |Cite
|
Sign up to set email alerts
|

Association between household food security and infant feeding practices in urban informal settlements in Nairobi, Kenya

Abstract: Studies in urban informal settlements show widespread inappropriate infant and young child feeding (IYCF) practices and high rates of food insecurity. This study assessed the association between household food security and IYCF practices in two urban informal settlements in Nairobi, Kenya. The study adopted a longitudinal design that involved a census sample of 1110 children less than 12 months of age and their mothers aged between 12 and 49 years. A questionnaire was used to collect information on: IYCF pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
51
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 28 publications
(49 reference statements)
17
51
1
2
Order By: Relevance
“…Finally, household food insecurity is associated with dietary diversity score of children. This finding is supported with other studies (13,25). It is known that HHFSS is one of the underlined cause of child malnutrition and hunger.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, household food insecurity is associated with dietary diversity score of children. This finding is supported with other studies (13,25). It is known that HHFSS is one of the underlined cause of child malnutrition and hunger.…”
Section: Discussionsupporting
confidence: 91%
“…Despite dietary diversity is a potentially and useful indicator for nutrient adequacy of a diet consumed by an individual and their nutritional status (9-11), complementary feeding continues as a challenge to good nutrition in children. For instance, in Nigeria 26.5% of under five children received adequately diversified diet (12), in Kenya 76% attained minimum meal frequency; 41% of the children attained a minimum dietary diversity; and 27% attained minimum acceptable diet (13). Similarly, inappropriate complementary feeding is a common practices in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of global initiatives and sufficient food production, this study reported that around 42% of HHs were food insecure. This is in line with reported 37.2-44.4% HHs food insecurity in the country (26,27); however the status of food insecurity is much higher than reported 14% (3), and lower when compared to 75% of Birhane et al (28) and 80.5% of Kenya (29). These inconsistencies could be explained by the socioeconomic and methodological differences.…”
Section: Discussionsupporting
confidence: 87%
“…In the context of food insecurity, we found that HHs use different coping strategies to deal with difficulties. This is supported by findings from qualitative and quantitative studies (25,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 63%
“…In spite of global initiatives and sufficient food production, our study reported that around 42% of HHs were food insecure. This is in line with reported 37.2-44.4% HHs food insecurity in the country (29,30); however the status of food insecurity is much higher than reported 14% (3), and lower when compared to 75% of Birhane et al (31) and 80.5% of Kenya (32). These inconsistencies could be explained by the socioeconomic and methodological differences.…”
Section: Discussionsupporting
confidence: 87%